(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article addresses theoretical and practical challenges in the automatic recognition of analytical verb forms in the Uzbek language. It analyzes criteria for distinguishing the grammatical function of auxiliary verbs, as well as disambiguating them from phraseological units and compound verbs. Special focus is given to the contextual differentiation of “converb + verb” constructions. Issues of segmentation and disambiguation essential for morphological analyzers are examined. Based on A. Hojiyev’s theory, the study aims to provide a scientific and practical foundation for machine translation and natural language processing systems.